Peningkatan Literasi Pengelolaan Keuangan Bagi Pelaku Usaha Penginapan di Objek Wisata Guci Kabupaten Tegal - Asrofi Langgeng Noerman Syah; Andri Widianto; Tantri Adithia Sabrina; Hana Yulinda Fithriyani; Wiyanti Wiyanti (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Community service activities carried out at the Guci Tourism Object in Tegal Regency aim to increase the understanding and knowledge of lodging business actors regarding the importance of managing business finances and preparing financial reports in accordance with the financial standards applicable in Indonesia, namely SAK EMKM. The problem that occurs is that lodging business actors do not have awareness of the importance of good financial management so that often transactions related to their business are not recorded properly, and there are transactions that should be recorded but are not carried out. This of course causes lodging businesses to not prepare financial reports. The solution provided is in the form of providing counseling and assistance in managing their business finances, starting from accounting records to preparing financial reports so that lodging business actors have sufficient knowledge in managing their business finances. The result of this service activity is that business actors gain an adequate understanding of business financial management and the importance of preparing financial reports in accordance with SAK-EMKM.